Particle tracking along kinta river, perak by using LABSWEâ¢ - Lim, Y.W. (World Academy of Research in Science and Engineering, 2020)
Kinta River is one of the major rivers spanning 17.1km from Tanjung Rambutan to Ipoh, Perak. Kinta River is important as both water source for local population as well as various economic activities. It is unavoidable that human activities cause siltation and sedimentation in the river. Suspended sediment is one of the main contributors to the turbidity problem in the river and it brings huge impact to the environment. This study aims to predict the transportation of sediment through displacement by application of LABSWEâ¢. The model developed provides information about the sediment location and mitigation solutions could be proposed to tackle the turbidity issue of the river. In this study, the LABSWEâ¢-Lagrangian Model is used to predict the particles transportation in water. It is shown the settling velocity generated by gravitational force could not be neglected. When the particle density increase, the corresponding sediment transportation increases. However, the density factors do not have significant effect to the particles as the particles are relatively small in grain size. Â© 2020, World Academy of Research in Science and Engineering. All rights reserved.